Singular perturbation decomposition-based ride quality control of elastic aircraft - LI Zhaoxing; WANG Xia; WANG Minwen; SHEN Jian; XU Bin (Xibei Gongye Daxue Xuebao, 2023)
Considering the reduction of ride comfort under wind disturbance, the ride quality control method based on singular perturbation decomposition is proposed. For the dynamic model of elastic aircraft, the singular perturbation theory is used to decouple the model into the rigid-slow subsystem and the flexible-fast subsystem. Considering the additional time-varying disturbance and aerodynamic uncertainty of the rigid subsystem, the disturbance observer is designed to estimate disturbance effect and the neural network is used to deal with model uncertainty. The adaptive robust control is constructed using the composite estimation information as feedforward compensation and the tracking error of pitch rate and normal overload as feedback design. For the flexible subsystem, a nonsingular terminal sliding mode controller is designed to achieve active vibration suppression. The ride quality control law of elastic aircraft is obtained by combining the control inputs of the rigid and flexible subsystems, and the additional normal overload and elastic mode can be quickly restrained and converged. Based on Lyapunov stability analysis, the uniformly ultimate boundedness of the system is proved. The simulation results show that the proposed method can reduce the additional normal overload at the key positions of the aircraft under discrete gust and atmospheric turbulence, and the riding quality of elastic aircraft is effectively improved.